Chekhov : the major plays - Chekhov, Anton Pavlovich, 1860-1904.; Dunnigan, Ann, tr. (New York : Penguin Book, 1982)
Contents.--Ivanov.--The Sea gull.--Uncle Vanya.--The three sisters.--The cherry orchard.
Includes bibliography.